THE ROLE OF INFORMATION FLOWS IN THE OPERATIONAL MANAGEMENT OF TRANSPORT: THE ROLE OF INFORMATION FLOWS IN THE OPERATIONAL MANAGEMENT OF TRANSPORT - Antonov, Anton; Nedev, Nikolai (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The management of transport flows is based on transmitting, receiving and processing the information related to them by applying the principles of the system approach. In a theoretical-applied aspect, it manifests itself as an economic activity for the development and implementation of methods for collecting, storing, processing and distributing information for specific functions and operations in transport infrastructure systems.